2018
DOI: 10.18203/2349-3933.ijam20181087
|View full text |Cite
|
Sign up to set email alerts
|

Study of impact of subclinical hypothyroidism on iron status and hematological profile

Abstract: Background: Thyroid hormones play an important physiological role to maintain balance of metabolism of entire human body. Erythrocyte abnormalities are frequently associated with thyroid disorder. Subclinical hypothyroidism, often a hidden entity, is associated with iron-deficiency anemia along with other hematological disorders.  Thyroid hormones have a crucial role in metabolism and proliferation of blood cells. Thyroid dysfunction has profound effects on blood cells such as anemia, alters RBC indices includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Our study showed decreased serum iron which was in accordance with the studies conducted by Dahiya K et al, 32 Eftekhari M et al, 33 Mishra A et al, 34 Cinemere H et al, 35 Onat A et al, 36 Bashboosh N et al, 37 and Kammak M et al, 38 Shukla A et al 39 showing anemia in hypothyroidism condition. Iron is considered a co-factor in catalysis of various important biological enzymes including Thyroperoxidase affecting the overall thyroid hormone metabolism.…”
Section: Et Al Mortoglou a Et Alsupporting
confidence: 90%
“…Our study showed decreased serum iron which was in accordance with the studies conducted by Dahiya K et al, 32 Eftekhari M et al, 33 Mishra A et al, 34 Cinemere H et al, 35 Onat A et al, 36 Bashboosh N et al, 37 and Kammak M et al, 38 Shukla A et al 39 showing anemia in hypothyroidism condition. Iron is considered a co-factor in catalysis of various important biological enzymes including Thyroperoxidase affecting the overall thyroid hormone metabolism.…”
Section: Et Al Mortoglou a Et Alsupporting
confidence: 90%
“…Many studies have attempted to study the relationship between subclinical hypothyroidism and iron deficiency anemia, but due to limited number of large cohort studies, a definitive status of this entity is still eluting the clinicians posing problems in management. Not many reports are available in literature to report on iron profile in hypothyroid patients (6).…”
Section: Total T 4 Had Positive Correlation With Tibc Andmentioning
confidence: 99%
“…It is known that thyroid hormones increase the oxygen capacity of the blood by increasing the production of erythropoietin (EPO) and improve perfusion through vasodilation after the increase of adrenomedullin. The hematopoietic system is one of the most affected systems in thyroid diseases, and anemia is one of the most common findings in these patients [1]. It is thought that hypothyroidism increases anemia by suppressing bone marrow and decreasing EPO production; and in the pathogenesis, thyroid hormone induces EPO gene expression by increasing hypoxia inducible factor 1 [2,3].…”
Section: Introductionmentioning
confidence: 99%